1998
DOI: 10.1590/s0004-282x1998000500003
|View full text |Cite
|
Sign up to set email alerts
|

Medication-taking behavior and drug self regulation in people with epilepsy

Abstract: -Objective: To study the most important characteristics of antiepileptic drug (AED) taking behavior in epileptic people. Methods: In a cross-sectional study, 45 consecutively seen patients answered a standardized questionnaire including questions about drug intake behavior. Results: Both genders were equally represented (22M x 23F). The mean age was 30.2 years. No specific characteristic were presented in all patients. The selfreported non-use of the drug at any moment one week before (self-reported non-adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
1
9
1
1
Order By: Relevance
“…The overall nonadherence rate to the AEDs, derived from the different measures, was 33%, which is within the reported range in international literature on the nonadherence to treatment in children with epilepsy of 3.5–58.0% (Lisk & Greene, ; Takaki et al., ; Shope, ; Hazzard et al., ; Gomes & Maia Filho, ; Kyngäs, ; Mitchell et al., ; Asadi‐Pooya, ; Conn et al., ; Modi et al., , ,b).…”
Section: Discussionsupporting
confidence: 67%
“…The overall nonadherence rate to the AEDs, derived from the different measures, was 33%, which is within the reported range in international literature on the nonadherence to treatment in children with epilepsy of 3.5–58.0% (Lisk & Greene, ; Takaki et al., ; Shope, ; Hazzard et al., ; Gomes & Maia Filho, ; Kyngäs, ; Mitchell et al., ; Asadi‐Pooya, ; Conn et al., ; Modi et al., , ,b).…”
Section: Discussionsupporting
confidence: 67%
“…[19] However, other studies reported a lower percentage of noncompliance of 40, 42, and 31.8%. [202122] All these studies used self-reported assessment of compliance and were also conducted at neurology clinic. There are studies reported higher rates of noncompliance using Morrisky scale.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐report measures are the most commonly used measurement in most studies of medication adherence (Osterberg & Blaschke, 2005), and self‐report methods such as surveys and interviews have been widely used to study adherence in epilepsy (Loiseau & Marchal, 1988; DiIorio & Henry, 1995; Gomes & Maia Filho, 1998; Mitchell et al, 2000; Paschal et al, 2005; Jones et al, 2006). Self‐report measures have the advantage of being low cost, noninvasive, and easily adaptable to a target population.…”
Section: Indirect Measuresmentioning
confidence: 99%
“…Instruments that specifically measure epilepsy treatment adherence are lacking, however, although more general self‐report measures may include items relevant to treatment adherence. Gomes & Maia Filho (1998) used a questionnaire that included one adherence question (“Did you forget or miss any of your medicine last week?”). Although judgment of adherence was based on that single question, other questions on the survey also addressed patient medication use behaviors.…”
Section: Indirect Measuresmentioning
confidence: 99%